Pengelolaan Sampah Organik Menggunakan Maggot Black Soldier Fly di Desa Sirnagalih, Kecamatan Tamansari, Bogor - Musthofa; Harley Dearmanson Girsang; Hafisah Jihan Azzahra; Anindita, Aurelia Shafa; Rini, Zayin Wahyu Setiyo; Imran, Nabila Nanda; Sitepu, Otniel; Ghifaari, Muhammad Aulia; Syahrazad, Rayhan (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The waste problem in Indonesia has become an urgent issue due to its serious impact on the environment and public health. According to data from the National Waste Management Information System, waste generation in West Java Province reaches 6.15 million tons per year, with Bogor Regency contributing the largest share at 1.02 million tons per year. One of the affected areas is Sirnagalih Village, Tamansari Subdistrict, which faces limited organic waste management facilities and low public awareness regarding waste segregation. The Community Service Program with Thematic-Innovation IPB University was implemented to improve public awareness and skills through education and demonstrations of Black Soldier Fly (BSF) maggot cultivation as an environmentally friendly and sustainable solution for organic waste management. The program involved Family Empowerment and Welfare cadres, youth organization, and community representatives through educational presentations, videos, and waste segregation simulations, followed by household-scale maggot cultivation demonstrations using simple materials such as plastic basins, non-woven fabric, and BSF larvae. Activities were monitored through observation, interviews, and regular follow-ups in targeted community units. The results indicated increased public awareness, as 4 out of 11 community units began practicing organic waste segregation and 100% of participants successfully cultivated maggots independently. Monitoring showed that maggots grew well and effectively reduced household organic waste volume, although challenges such as odor, humidity, and pest attacks remained. Solutions were addressed using natural odor control techniques, feed adjustments, and the establishment of community-based management groups at the community units level.